Literature Review of Total Productive Maintenance (TPM) and Recommendations for Application in the Defense Industry - Mutaqiem, Agus; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
Total Productive Maintenance (TPM) has been applied in various industries to increase productivity. The purpose of this article is to explore the benefits of implementing Total Productive Maintenance (TPM) in various industries and provide recommendations to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 30 international journal articles published from 2010 to 2021 regarding the implementation of Total Productive Maintenance (TPM) in various industrial sectors and the defense industry. The analysis used used 25 content analyzes of journal articles, which had been collected and then looked for similarities and differences and then discussed to draw conclusions. The results of the literature review analysis state that the application of Total Productive Maintenance (TPM). The results of the literature review analysis state that the effect of the application of TPM contributes to factory performance. These effects are reduced costs, decreased quality, smoother product delivery, and increased productivity. improve machine and equipment performance, reduce reject and rework and increase production output. The implementation of TPM increases productivity due to good machine maintenance management, demonstrating the increased performance provided by these pillars. Simulation of the proposed maintenance process can reduce the average waiting time between failures which can be reduced and increase the available time. Based on the literature review, TPM is recommended to be applied to the defense industry